Genesis of equifinality and multifinality of open systems - Gribkov, Andrei Armovich (Философская мысль, 2023)
The subject of research in the article are the properties of equifinality and multifinality of open systems, widely spread in all subject areas, at all levels of organization: in physical, chemical, biological, economic, social, etc. open systems. Equifinality is a dynamic property of a system that realizes movement (transition) in different ways from different initial states to the same final state. Multifinality is the dynamic property of a system to reach fundamentally different final states under insignificant changes in initial conditions. Examples of realization of the properties of equifinality and multifinality in systems of different nature: physical, biological, economic are considered. The genesis of these properties is investigated. On the basis of the study of the genesis of the properties of equifinality and multifinality its commonality is revealed: both properties are a consequence of the transformation of quasi-continuous quantitative changes into discrete qualitative forms, as well as the limited variety of these forms caused by isomorphism. The origin of the multiplicativity property (increased sensitivity to variation of input parameters) and its difference from multifinality are revealed. The multiplicativity property is manifested in systems with unequal stability, including those possessing positive feedback mechanisms. In some systems, such as meteorological mathematical models, the properties of multiplicativity and multifinality appear simultaneously and cannot be unambiguously distinguished.